Duloxetine-related posterior reversible encephalopathy syndrome: A case report. Issue 33 (August 2016) - Zappella, Nathalie; Perier, François; Pico, Fernando; Palette, Catherine; Muret, Alexandre; Merceron, Sybille; Girbovan, Andrei; Marquion, Fabien; Legriel, Stephane
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Posterior reversible encephalopathy syndrome (PRES) has well-established links with several drugs. Whether a link also exists with serotonin–norepinephrine reuptake inhibitor such as duloxetine is unclear. Methods: We report on a patient who developed PRES with a coma and myoclonus related to hypertensive encephalopathy a few days after starting duloxetine treatment. Magnetic resonance imaging was performed and catecholamine metabolites assayed. Results: The patient achieved a full recovery after aggressive antihypertensive therapy and intravenous anticonvulsant therapy. Conclusions: The clinical history, blood and urinary catecholamine and serotonin levels, and response to treatment strongly suggest that PRES was induced by duloxetine. Duloxetine should be added to the list of causes of PRES.